TechGen Corporation : Portable Air Compressor / Muhammad Aqim Nazeef Azaha ...[et al.] - Azaha, Muhammad Aqim Nazeef; Mustaffa, Muhamad Amierul; Bakri, Muhammad Azim; Ahzmi, Muhammad Alif Hafiz; Noor Hisam, Fatin Nadia; Azami, Muhammad Mikail Farabi (2016)
As for the business, we are providing a newly invented technology which is portable air compressor. As we move forward towards the future, technology grow and become much better. Providing this machines will give a lot of advantage for its consumer as it can make their emergency problem much easier to be completed. We are going to provide this machine to the entire nations so that this technology can be used by all people around this country.